Spatial Qualitative Analysis of the Marine Heritage Tourism in Bontoharu-Bontosikuyu District, The Selayar Regency - Latif, Aqilah N. Khaerani; Lisani, Nur; Mutaqim, Zaenul; Matulluayli, Nugi (ASEAN Journal on Hospitality and Tourism, 2024)
Marine cultural tourism, a developing tourism mode, has grown in popularity among tourists in recent years, indicating broad market prospects (Zheng et al., 2017). Selayar Islands Regency is an international commerce route believed to have existed since 1820. According to preliminary data, a shipwreck with ceramics and money coins was discovered in the Bontosikuyu District and its surrounds in China. It is believed that these coins circulated throughout the archipelago between the 11th and 14th centuries. However, the vast potential has not been realized. In addition, there is a risk of local populations exploiting maritime cultural heritage objects for economic gain. This study is to investigate the potential of marine heritage as a new tourism destination in the Selayar Islands Regency. This research methodology is spatial qualitative, with spatial analysis using the ArcGIS application followed by qualitative identification of tourism potential using the 3A approach (attractions, amenities, accessibility). The study identified numerous prospective places based on interviews with stakeholders and study literature for marine heritage tourism that could serve as a tourist route. The proposed route has yet to be tested. Its potential is based solely on observation results; literature reviews; and conversations with stakeholders. This research aims to identify prospective maritime heritage routes in the Selayar Islands Regency. The study's findings indicate that the potential for marine heritage tourism packages in Selayar Regency is enormous but due to a lack of attention, it requires significant improvement and development in terms of attractions, accessibility, and amenities.